Floral morphology and reproduction mode determine feijoa (Acca sellowiana) as a facultative xenogamous species - Cintia Finardi; Marcia Regina Faita; Afonso Inácio Orth; Rubens Onofre Nodari (Acta Biológica Catarinense, 2025)
Different accessions from the active germplasm bank (São Joaquim, SC, Brazil) of feijoa or pineapple-guava (Acca sellowiana) were evaluated, with the aim of determining the number of pollen grains and ovules, including the pollen:ovule ratio and its association with the distance between stigma and stamens (SSD) and the distribution of stamens in the flower. The results demonstrated that 21.6%, 52.7% and 25.6% of the 73 accessions had an average SSD of less than 0.5 cm, 0.5 to 0.9 cm, and equal or more than 1.0 cm, respectively, thus fitting a 1:2:1 ratio among the three classes (χ2 = 2.64; 0.30<P<0.50). An equal distribution of two types of stamens, radial and random, in the flower was also verified in a 1:1 ratio. This dual analysis also showed that the distribution of stamen types in the flower and SSD classes occurs independently. Radial type flowers had an average of 47.4 anthers, while flowers with random distribution had an average of 67.7. In flowers with random stamen distribution, more ovules were observed, as well as higher pollen:ovule ratio compared to flowers with radial stamen distribution. These results suggest that A. sellowiana exhibits a xenogamous mode of reproduction with a predominance of allogamy